Kemampuan Organisasi dalam Keberlanjutan dan Ketahanan untuk Meningkatkan Manajemen Kelangsungan Bisnis : Tinjauan Literatur - Damis Veri Budianto; Komarun Zaman (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study investigates these linkages to deepen understanding of the topic and to outline potential directions for future research. Using bibliometric and content analysis drawn from the Web of Science and Scopus databases, covering the period from 1998 to 13 May 2021, the study reveals key insights. The findings show a reciprocal relationship between organizational sustainability capabilities and organizational resilience capabilities; however, evidence connecting both to business continuity management is still insufficient. The results also highlight four clusters of relationships: (1) the progression from Risk Management toward Business Continuity Management and Organizational Resilience; (2) the interaction between Resilience and Business Continuity practices; (3) the role of Business Continuity in fostering Innovation and Sustainability; and (4) Dynamic Capabilities that support Organizational Sustainability and Organizational Resilience to strengthen Business Continuity Management. Furthermore, several phases were identified to explain how sustainability and resilience capabilities influence business continuity management in the face of disruptive events